A review on tool supports for security requirements engineering - Sidek, Safiah (2013)
Capturing the right security requirements is crucial when developing a security software. Poor elicited security requirements can lead to a failure in software development, thus it needs to be accurately defined. This study evaluates various security requirement engineering tools and analyses the existing gaps in security requirement engineering tools. Based on a literature search conducted manually, we report our findings from the review and analysis of different studies of security requirements engineering tool. Consequently, the gaps and motivations found from this literature study are discussed. Future directions of this study is to develop a more useful tool that can perform a better function in capturing security requirements are also discussed.